Teacher Performance Post-Covid-19: A Study of Workload, Leadership Style, and Teacher Work Discipline at SMAN 21 Tangerang District - Hikmah Perkasa, Didin; Mulyanto, Hery; Imelda Novia Susiang, Maria; Dhyan Parashakti, Ryani; Nina Rostina, Cut (KnE Social Sciences, 2023)
Achieving good teacher performance will be determined mainly by leadership characteristics. The Covid-19 pandemic outbreak has affected business organization management, including organizations in schools. Each leader has their style in human resources management, likewise in schools. Teaching and learning activities that were initially face-to-face switched to using remote applications such as zoom meet, google meet, and other online teaching media or applications. This study aims to analyze the factors that influence the success of the educational field from the point of view of the teaching staff. The success of the education world in a nation is inseparable from the internal role of school stakeholders, particularly teachers. A teacher’s success can be judged by how well the resulting performance is. That every teacher has a teaching workload that must be passed in teaching and learning activities to meet teaching performance. Workloads are in the form of activities that must be completed within a certain time frame. A leader’s duty is to motivate teachers to achieve maximum performance. A teacher who has job discipline will be able to achieve performance following the allotted time. This study critically reviews the factors that affect teacher performance. Finally, this study will propose a model of the relationship between leadership style, workload, and discipline in predicting teacher performance post- Covid-19. Keywords: teacher performance, workload, leadership style, work discipline